Globalization Without Global Money. The Double Role of the Dollar as National Currency and as World Currency and its Consequences - Stephan Schulmeister (Austrian Institute of Economic Research (WIFO), 1998)
Since the end of World War II the dollar has played a double role, it has served as national currency of the US and as key currency of the world economy. As world currency the dollar serves as "numeraire" for supranational flows and stocks since commodities as well as most international assets/liabilities are priced in dollars. Consequently, changes in the interest rate and the exchange rate of the dollar not only impact upon the economic relations between the US and the rest of the world, but influence also the relative prices between commodities and manufactures, the terms of trade between industrial and developing countries, the speed of inflation and deflation in world trade and the level of the real interest on international debts. As a consequence, the instability of the exchange rate as well as of the interest rate of the dollar since the early 1970s has had a tremendous impact on the international economy (due to the dollar as world currency); at the same time, this instability has been mainly caused by the "inward looking" policy of the US (due to the dollar as national currency). The most important events in postwar economic development - from the collapse of the Bretton Woods system and the subsequent oil price "shocks" to the international debt crisis in the early 1980s and the East Asian drama in the late 1990s - are linked to the double role of the dollar and the related conflict between the need of stable monetary conditions for the world economy as a whole and the national-oriented economic policy of the US.
Keywords: 330; US-Dollar; Reservewährung; Wechselkurspolitik; Internationaler Finanzmarkt; Globalisierung; Welt